2012
DOI: 10.1007/s11920-012-0319-2
|View full text |Cite
|
Sign up to set email alerts
|

Staging and Neuroprogression in Bipolar Disorder

Abstract: The apparently progressive nature of a considerable proportion of cases of bipolar disorder (BD) has been acknowledged in recently proposed clinical staging models. This has been part of an attempt to facilitate and refine diagnosis, treatment selection, and establish a prognosis. The study of the progressive nature of some cases of BD has given raise to the hypothesis of neuroprogression, which postulates that different stages of BD are associated with distinct neurobiological underpinnings. Given that BD may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 90 publications
4
68
2
4
Order By: Relevance
“…6,8,[11][12][13] Moreover, changes in cognitive functions are more marked in advanced stages of the disease than in controls and in patients in the initial phases of this psychiatric disorder. 8 Recent studies also showed that cognitive dysfunction and functional deterioration persist even during the euthymic periods in the advanced stages of the disease.…”
Section: 910mentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,[11][12][13] Moreover, changes in cognitive functions are more marked in advanced stages of the disease than in controls and in patients in the initial phases of this psychiatric disorder. 8 Recent studies also showed that cognitive dysfunction and functional deterioration persist even during the euthymic periods in the advanced stages of the disease.…”
Section: 910mentioning
confidence: 99%
“…5 A growing body of evidence suggests that BP is a progressive disease. [6][7][8] In 1899 Emil Kraepelin found that the intervals between mood episodes become successively shorter as the number of previous episodes increases. The same author described that, after a certain number of recurrences, episodes tend to occur more spontaneously, in contrast with initial episodes, which are usually triggered by psychosocial stress factors.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The clinical progression described above is hypothesized to be subserved by neurobiological changes, the so-called neuroprogression. [13][14][15] This hypothesis is based on observations that brain morphology alterations, such as reductions in volume and gray matter and enlargement of ventricles, are more pronounced in chronic patients than in individuals with fewer episodes. Similarly, evidence indicates a different profile in peripheral biomarkers linked to BD pathophysiology and a wider range of abnormalities in such biomarkers in these patients, 16 including differences in levels of neurotrophins, specifically the brain-derived neurotrophic factor, and inflammatory and oxidative stress markers.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of such toxicity becomes more evident at later stages of illness (33)(34)(35)(36)(37)(38), causing less efficient cellular resilience mechanisms that may be leading to a pathological reorganization between different brain areas (39). This rewiring of the brain within the context of clinical and cognitive deterioration is called "neuroprogression".…”
mentioning
confidence: 99%
“…This rewiring of the brain within the context of clinical and cognitive deterioration is called "neuroprogression". Neuroprogression is suggested to be associated with the impaired resilience to stress in patients with BD (39). In sum, it has been proposed that mood episodes generate an extra load on the allostasis that is responsible for the illness progression (15).…”
mentioning
confidence: 99%